An economic evaluation of first-line cryoballoon ablation versus antiarrhythmic drug therapy for the treatment of paroxysmal atrial fibrillation from a German healthcare payer perspective - Malte Kuniss; Lucy Hillcoat; Joe Moss; Florian Straube; Jason Andrade; Oussama Wazni; Gian Battista Chierchia; Lukas Schwegmann; Eleni Ismyrloglou; Alicia Sale; Stuart Mealing; Tom Bromilow; et al. (BMC Health Services Research)
Abstract Background Three recent randomized controlled trials demonstrated that, in patients with symptomatic paroxysmal atrial fibrillation (PAF), first-line pulmonary vein isolation with cryoballoon catheter ablation reduces atrial arrhythmia recurrence compared to initial antiarrhythmic drug (AAD) therapy. This study aimed to evaluate the cost-effectiveness of first-line cryoablation compared to first-line AADs from a German healthcare payer perspective. Methods Individual patient-level data from 703 participants with untreated PAF enrolled into three randomized clinical trials (Cryo-FIRST, STOP AF First and EARLY-AF) were used to derive parameters for the cost-effectiveness model (CEM). The CEM structure consisted of a hybrid decision tree and Markov model. The decision tree (one-year time horizon) informed initial health state allocation in the first cycle of the Markov model (40-year time horizon; three-month cycle length). Health benefits were expressed in quality-adjusted life years (QALYs). Cost inputs were sourced from German diagnosis-related groups and the Institute for the Hospital Remuneration System (InEK). Costs and benefits were discounted at 3% per annum. Results Cryoablation was cost-effective, incurring ~ €200 per patient while offering an increase in QALYs (~ 0.18) over a lifetime. This produced an average incremental cost-effectiveness ratio of ~ €1,000 per QALY gained. Individuals were expected to receive ~ 1.2 ablations over a lifetime, regardless of initial treatment. However, those initially treated with cryoablation as opposed to AADs experience 0.9 fewer re-ablations and a 45% reduction in time spent in AF health states. Conclusion Initial rhythm control with cryoballoon ablation in symptomatic PAF is a cost-effective treatment option in a German healthcare setting.